The concept of temporary protection in the EU and Turkey - Kurt, Ekin (My University, 2022)
Toplu halde yabancı bir ülkeye sığınan kişiler geçici koruma statüsü alabilirler fakat geçici koruma gerektiren hallerin tanımını yapmak oldukça önemlidir. Geçici koruma terimi, diğer uluslararası koruma statüsünden oldukça farklıdır. Bu araştırmada Cenevre Sözleşmesi, geçici koruma statüsünün özünü anlamak açısından sığınma hukukuna ilişkin temel antlaşma olarak ele alınmaktadır. Uluslararası hukuk, Avrupa Birliği hukuku ve Türk hukukunda iltica kavramının tarihsel gelişimi ışığında, geçici koruma kavramının ortaya çıkışı incelenmiştir. Geçici koruma statüsünün kavramsal açıklaması ile amacı, koşulları, kişiler açısından kapsamı, geçici koruma statüsünün usulü ve süresi ile kişilere sağladığı haklar ayrıntılı olarak incelenmiştir. Sığınmacıların geçici koruma sahibi olarak kabul edilmesi, prosedürün tamamlandığı anlamına gelmemektedir. Aksine, ev sahibi ülke statü sahiplerine sadece yaşama hakkı vermekle kalmamalı, aynı zamanda her bir kişinin insanlık onurunu da dikkate almalıdır. Kitlesel akınların neden olduğu krizlerde temel haklara erişime dair sorunları çözmek için, geçici koruma kavramı ele alınırken insan hakları temelli bir yaklaşım kullanılmalıdır. Bu nedenle, AB ve Türkiye'de geçici koruma kavramına insan hakları temelli bir yaklaşımı anlamak için temel anlaşmalar ışığında her bir mevzuatın olumlu yönleri ve eksiklikleri karşılaştırılmalı olarak ortaya konmuştur.

People who have taken refuge in a foreign country en masse may receive the status of temporary protected persons, however, it is critical to identify the situations that require temporary protection. In this research, the Geneva Convention is considered as the fundamental treaty regarding asylum law as understanding the essence of the temporary protection status. In light of the historical development of the concept of asylum in international law and international protection law, European Union law and Turkish law, the emergence of the concept of temporary protection has been examined. Through a conceptual explanation of temporary protection status, its purpose, conditions, scope in terms of individuals, procedure and duration of temporary protection status and the rights it confers on individuals are examined in detail. Accepting asylum seekers as temporary protection holders does not mean that the procedure is complete. On the contrary, the host country must not only give status holders the right to live, but also take into account the human dignity of each person. When considering the concept of temporary protection, a human rights-based approach should be adopted in order to solve the problems of access to fundamental rights in crisis situations caused by mass influxes. Therefore, shortcomings of each legislations were compared to each other in the light of fundamental treaties in order to understand human rights-based approach on the concept of temporary protection in the EU and Turkey. Thus, the arguments in favour of and against the legal sources in the EU and Turkish legislation by comparison are revealed.
Keywords: Avrupa Birliği; Cenevre Sözleşmesi; European Union; Geçici Koruma; Geneva Convention; Injunctions; İhtiyati tedbir; Kitlesel Akın; Mass Influx; Temporary Protection; The Directive; The Regulation; Turkey; Türkiye; Yönerge; Yönetmelik